Development of Sustainability Assessment Framework in Hydropower sector - Nur Soliha, Sahimi; Faiz, Mohd Turan; Kartina, Johan (IOP Publishing, 2017)
Nowadays, Malaysian demand in energy sector was drastically increase due to technological developments. Since, hydropower is one of potential renewable energy source in Malaysia. The largest electricity utility company, Tenaga Nasional Berhad was provide an electricity to more than seven million people via independent suppliers in peninsular Malaysia and Sabah by intended a potential sustainable hydropower system. In order to increasingly the power capacity from current use, 1882 MW to more than 3000 MW by years 2020. In this study, the environmental issues and also the penalty to the responsible company especially on Tenaga Nasional Berhad (TNB) towards their project or business are one of the problems. Other than that, every project or business has to prepare a sustainability statement or sustainability report as vital to Bursa Malaysia Securities Berhad under their listing requirements. Next, the sustainability performance on their project cannot be determined to achieve the key performance indicators (KPI) satisfaction from Government, stakeholder or any responsible agencies. This study presents an exhaustive review of these studies and suggests a direction for future developments. Sustainability Assessment framework or self-assessment is decidedly as a significant framework to assist towards sustainability reporting and to produce a Sustainability index for Hydropower sector using a mathematical model study. The results reveal that, the quantitative measurement from Sustainability Assessment framework to Systematic Sustainability Asssesment tool can be produce. In doing so, it is possible to improve the performance of the project especially in hydropower planner.